PENGARUH BAHAN BAKU, KEWIRAUSAHAAN DAN PENGALAMAN KERJA TERHADAP PRODUKSI DAN PENDAPATAN INDUSTRI KULINER RUMAH MAKAN - Prana Cita, I Made Andre; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The rapid development of the restaurant is currently an opportunity for the younger generation to be able to open culinary business and can combine innovations to attract consumers. This study aims to find out the influence of raw materials, entrepreneurship and work experience on the production and income of the culinary industry in Denpasar. The population in the study were all restaurant businesses. The sample used was 76 with Simple Random Sampling. Path analysis techniques are used. The results of the study show that raw materials and entrepreneurship have positive and significant effect on industrial production, work experience has no effect on industrial production. Raw materials, entrepreneurship, and production have positive and significant effect on income, work experience has no effect on income. Raw materials and entrepreneurship have indirect effect on income through production, work experience does not have indirect effect on income through the production of the restaurant's industry.